Using rotor inertia as stored energy in below rated wind farms to provide primary frequency response. Issue 2 (September 2020) - Cole, Matthew; Stock, Adam; Leithead, W.E.; Amos, Lindsey
Abstract: The objective of this work is to present a method for providing ancillary services to the grid with minimal reduction in power output from the turbines in a wind farm by utilising the stored energy in the turbine rotors. By first demonstrating an approach of extracting energy from a single turbine's rotor, it can be shown that this could lead to increased energy yields while still being able to provide primary response provision compared to curtailing each turbine by 10%. Following this, when this approach is tested at the wind farm level there is considerable evidence that considering the energy stored in the turbine rotors across a wind farm can lead to increases in energy capture while not significantly increasing damage equivalent loads for either towers or blades.